Evaluations on the miscibility of the mixtures of poly(2,6-dimethyl-1,4-phenylene oxide) and a copolyester of bisphenol-A - Sakar, Dolunay; Cankurtaran, Ozlem; Karaman, Ferdane (WILEY, 2009)
Inverse gas chromatography (IGC) was used to analyze the miscibility of binary mixtures of poly(2,6-dimethyl-1,4-phenylene oxide) (PPO) and a copolyester of bisphenol-A with terephthalic and isophthalic acids (50/50) (PAr) in three compositions. The glass transition temperature (T-g) was determined from the slope change on the retention diagrams of some solvents on the polymers and their binary mixtures. Single T(g)s of the mixtures suggested that PAr and PPO are miscible. Separately, IGC data were used to determine the solvent-independent polymer-polymer interaction parameters of the binary mixtures above their T(g)s by means of some methods proposed by several authors. The magnitudes of the interaction parameters and shifting of ester carbonyl peak of PAr on the Fourier transform infrared (FTIR) spectra suggested that these polymers were miscible. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: miscibility; blends; thermodynamics; polymer-polymer interaction parameter; inverse gas chromatography; POLYMER; CHROMATOGRAPHY; Polymer Science